(untitled) (Sains Humanika, 2021)
The aim of this research is to discover the correlation between anxiety level of retirement and self-adaptation, social support, years of service and age on Indonesian National Army Soldiers at Kodim (Military District Command). This research used a quantitative research method carried out on 97 soldiers at Kodim. The sampling method used cluster random sampling. This research used three measurement scales. The anxiety of retirement scale consisted of 23 items with the coefficient correlation starts from 0.377-0.653 and a reliability coefficient of 0.723. The social support scale consisted of 29 items with a coefficient correlation starts from 0.369–0.775 and a reliability coefficient of 0.936. The self-adjustment scale consisted of 40 items with a coefficient correlation starts from 0.325-0.249 and a reliability coefficient of 0.959. There are five models to be analyzed in this study, using regression analysis of two predictors and partial correlation with the assistance of SPSS version 19.0. The results of the analysis of the model 1 (social support, adjustment and anxiety), model 2 (social support, adjustment, word period and anxiety), model 3 (social support, adjustment, age and anxiety) and model 4 (social support, adjustment, age, years of service and anxiety) show a significant correlation between all variables tested. Hypothesis 1 to 4 are accepted. Meanwhile, the result of the hypothesis model 5 (years of service, age and anxiety) shows that there is no correlation between all variables tested. Fifth hypothesis is rejected.